Commercial Pressure Retarded Osmosis Systems for Seawater Desalination Plants - Ryo Makabe; Tetsuro Ueyama; Hideyuki Sakai; Akihiko Tanioka (Membranes, 2021)
The development of renewable energy technologies is of global importance. To realize a sustainable society, fossil-resource-independent technologies, such as solar- and wind-power generation, should be widely adopted. Pressure retarded osmosis (PRO) is one such potential renewable energy technology. PRO requires salt water and fresh water, both of which can be found at seawater desalination plants. The total power generation capacity of PRO, using concentrated seawater and fresh water, is 3 GW. A large amount of energy is required for seawater desalination; therefore, the introduction of renewable energy should be prioritized. Kyowakiden Industry Co., Ltd., has been working on introducing PRO to seawater desalination plants since 2001 and is attracting attention for its ongoing PRO pilot plant with a scale of 460 m3/d, using concentrated seawater and treated sewage water. In this study, we evaluated the feasibility of introducing PRO in existing desalination plants. The feasibility was examined based on technology, operation, and economy. Based on the number of seawater desalination plants in each country and the electricity charges, it was determined whether the introduction of PRO would be viable.